Personality and workplace bullying : role of the big five personality traits in predicting workplace bullying perpetrators in South Africa - Van der Westhuizen, Mari (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.